Effects of transcutaneous electrical acupoint stimulation on ovarian reserve of patients with diminished ovarian reserve in in vitro fertilization and embryo transfer cycles. Issue 12 (12th October 2015) - Zheng, Ying; Feng, Xiaojun; Mi, Hui; Yao, Yi; Zhao, Yu; Li, Jing; Jiao, Jiao; Gong, Ailing; Sun, Wei; Deng, Xiaohui
Abstract: Aim: The aim of this study was to investigate the effect of transcutaneous electrical acupoint stimulation (TEAS) on ovarian reserve in patients with diminished ovarian reserve undergoing in vitro fertilization and embryo transfer. Material and Methods: A total of 240 patients were randomly divided into the Han's acupoint nerve stimulator TEAS treatment (TES), comforting false Han's placebo (FHP), artificial endometrial cycle treatment (AEC), and control (CON) groups. Results: Fifty‐six patients in TES, 56 in FHP, 54 in AEC, and 60 in CON fulfilled the study, respectively. Antral follicle count and anti‐Müllerian hormone levels were increased, whereas the estradiol level, follicle‐stimulating hormone level, and follicle‐stimulating hormone/luteinizing hormone ratio were significantly decreased after treatment in the TES and AEC groups. After treatment, the number of oocytes retrieved and average number of embryos transferred were higher in the TES and AEC than in the CON and FHP groups. Clinical pregnancy rate in the TES group was markedly higher than values obtained for the other three groups. Conclusion: TEAS and AEC treatments could improve basal endocrine levels in patients, and increase the number of oocytes retrieved and high‐quality embryos. TEAS treatment could improve the clinical pregnancy rate in patients with decreased ovarian reserve during in vitro fertilization and embryo transfer cycles.